Arabic Orthography: Development of Kahoot and Gamification Website-Based Writing Materials to Improve Understanding of Writing Rules - Miolo, Mukhtar I.; Hula, Ibnu Rawandhy N.; Laiya, Fidya Fadila Safriana (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aims to design and develop Arabic orthography instructional materials using the Kahoot platform integrated with gamification to enhance students’ understanding of Arabic writing rules. The research employed a Research and Development (R&D) approach using the ADDIE model, involving 60 students from MAN 1 Boalemo. The development process included needs analysis, content design, material digitization, validation, implementation, and evaluation. Expert validation confirmed high feasibility with ratings of 88% (media expert), 83% (content expert), and 92% (language expert). Trial implementation showed strong acceptance from both teachers (89%) and students (80%). Learning effectiveness was measured through pretest and posttest, with mean scores improving from 58.85 to 84.20. Paired sample t-tests indicated statistically significant improvement (p < 0.05), while normality tests confirmed data distribution was normal. The results suggest that gamified instructional design using Kahoot effectively boosts student motivation, engagement, and mastery of Arabic orthography. This work contributes to the field by offering an engaging, scalable, and pedagogically sound solution for Arabic language learning in digital environments.